Does hot weather affect human fertility? - Alan Barreca (IZA World of Labor, 2017)
Research finds that hot weather causes a fall in birth rates nine months later. Evidence suggests that this decline in births is due to hot weather harming reproductive health around the time of conception. Birth rates only partially rebound after the initial decline. Moreover, the rebound shifts births toward summer months, harming infant health by increasing third trimester exposure to hot weather. Worse infant health raises health care costs in the short term as well as reducing labor productivity in the longer term, possibly due to lasting physiological harm from the early life injury.
Keywords: 330; fertility; birth rates; temperature; climate change